Deep-sea benthic foraminifera record of the last 1500 years in the North Aegean Trough (northeastern Mediterranean): A paleoclimatic reconstruction scenario. (January 2020) - Dimiza, M.D.; Fatourou, M.; Arabas, A.; Panagiotopoulos, I.; Gogou, A.; Kouli, K.; Parinos, C.; Rousakis, G.; Triantaphyllou, M.V.
Abstract: A 1500-year, high-resolution deep-sea benthic foraminifera record from the Athos Basin of the North Aegean Trough (northeastern Mediterranean) has been analyzed for the development of a paleoclimatic scenario. The data analysis points out that the quantity and quality of the seafloor's organic matter could be a crucial controlling factor for the faunal succession. During 550–1000 AD (within the Medieval Climate Anomaly), the relatively high benthic foraminiferal accumulation rates together with the predominance of meso-eutrophic taxa, such as Bolivina dilatata / spathulata, may be interpreted as the result of high precipitation. Consequently, increased riverine discharges into the North Aegean Sea and the associated warm climatic conditions appear to persist for a long time and are related to a negative phase of the North Atlantic Oscillation. Later on, the establishment of an oligo-mesotrophic seafloor environment is documented by the diminishing benthic foraminiferal accumulation rates associated with an increment in the abundances of Gyroidinoides altiformis . During a colder phase of the Little Ice Age (17th century), the relative abundances of the opportunistic foraminiferal species Bulimina inflata and Bulimina marginata can be related to high marine productivity, most probably due to enhanced winter mixing conditions. Finally, during the last 100 years, a faunal shift to eutrophication preferent species, and the persistent occurrence of Chilostomella mediterranensis, reflects a pronounced change in trophic conditions, characterized by high amounts of potentially low-quality organic matter in the seafloor, which are the result of a gradual temperature increase accompanied with enhanced terrigenous inputs.